2005
DOI: 10.1007/bf03167180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen on the NMR relaxation properties of crude oils

Abstract: Nuclear magnetic resonance relaxation measurements of bulk fluids provide a sensitive probe of the dynamics of molecular motion. Dissolved oxygen can interfere with this technique as its paramagnetic nature leads to a reduction of the paramagnetic relaxation times of the fluids. We studied this effect for the relaxation properties of crude oils that are in general characterized by a distribution of relaxation times. The samples were stock tank oils that have been exposed to air. We compared T~ and ir relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 9 publications
(9 reference statements)
5
21
0
Order By: Relevance
“…higher alkanes, narrow range of aromatics, etc. Chiarotti et al [4] and later Chen et al [12] and Mutina and Hürlimann [14] attributed a discrepancy between published bulk fluid relaxation times to paramagnetism of dissolved oxygen. Thus, the observed relaxation rate is the linear sum of two processes, bulk relaxation time of pure fluid, , defined by dipolar interactions and rotational coupling of spins and relaxation due to paramagnetic species—oxygen gas in this study, :For liquid normal alkanes under typical ambient conditions (at atmospheric pressure and temperature interval of interest, from approx.…”
Section: Correlation Of Diffusivity Viscosity and Nmr Relaxationmentioning
confidence: 99%
See 3 more Smart Citations
“…higher alkanes, narrow range of aromatics, etc. Chiarotti et al [4] and later Chen et al [12] and Mutina and Hürlimann [14] attributed a discrepancy between published bulk fluid relaxation times to paramagnetism of dissolved oxygen. Thus, the observed relaxation rate is the linear sum of two processes, bulk relaxation time of pure fluid, , defined by dipolar interactions and rotational coupling of spins and relaxation due to paramagnetic species—oxygen gas in this study, :For liquid normal alkanes under typical ambient conditions (at atmospheric pressure and temperature interval of interest, from approx.…”
Section: Correlation Of Diffusivity Viscosity and Nmr Relaxationmentioning
confidence: 99%
“…The latter found that the modified theory of Torrey [35] describing relaxation by dipolar translational diffusion (i.e scalar coupling effect is negligible) is sufficient to describe the effect of dissolved gaseous oxygen on relaxation in water and potentially in liquids in a more broad sense. Chen et al [12] and Hürlimann et al [14] suggested a simple concept of oxygen relaxation enhancement by considering observed relaxation time as the arithmetic sum of two relaxation terms, see Eq. 4: (1) bulk relaxation of pure deoxygenated fluid, 1/ and (2) an oxygen enhanced relaxation term, 1/.…”
Section: Oxygen Effect On Diffusion-relaxation Correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…The deoxygenation procedure was well described in the study of Mutina and Hürlimann (2005) (Keszler, Kriska, & Németh, 2000;Mutina & Hürlimann, 2005). One cycle of deoxygenation procedure included the following steps: 1.…”
Section: Oleic Acid Storage Assaymentioning
confidence: 99%